2022
DOI: 10.3390/ijms23147918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mortalin on Scar Formation in Human Dermal Fibroblasts and a Rat Incisional Scar Model

Abstract: Wound healing is a complicated cascading process; disequilibrium among reparative processes leads to the formation of pathologic scars. Herein, we explored the role of mortalin in scar formation and its association with the interleukin-1α receptor using in vitro and in vivo models. To investigate the effects of mortalin, we performed an MTT cell viability assay, qRT-PCR, and Western blot analyses, in addition to immunofluorescence and immunoprecipitation studies using cultured fibroblasts. A rat incisional wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Furthermore, the number of M1 macrophages begins to increase at 0-2 days after injury, peaks at 7-14 days after injury, and decreases significantly at 14-28 days after injury ( 72 ). This finding indicates that M1 cells secrete many inflammatory mediators in the early stage of normal scar formation ( 74 , 75 ). During the transition from the inflammatory phase to the proliferative phase of wound healing, M1 cells are transformed into the M2 phenotype by the phagocytosis of neutrophils or the change of local wound microenvironment ( 76 , 77 ).…”
Section: Cutaneous Wound Healing and The Mechanism Of Psmentioning
confidence: 83%
“…Furthermore, the number of M1 macrophages begins to increase at 0-2 days after injury, peaks at 7-14 days after injury, and decreases significantly at 14-28 days after injury ( 72 ). This finding indicates that M1 cells secrete many inflammatory mediators in the early stage of normal scar formation ( 74 , 75 ). During the transition from the inflammatory phase to the proliferative phase of wound healing, M1 cells are transformed into the M2 phenotype by the phagocytosis of neutrophils or the change of local wound microenvironment ( 76 , 77 ).…”
Section: Cutaneous Wound Healing and The Mechanism Of Psmentioning
confidence: 83%
“…Myofibroblasts are known to play a major role in wound healing and abnormal scar formation, and α‐SMA is the most reliable and widely used marker for the differentiation of fibroblasts into myofibroblasts, 5,31,32 and is assessed by western blot analysis 33–36 . Transforming growth factor‐β1 (TGF‐β1) is known to be a strong inducer of myofibroblast differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Myofibroblasts are known to play a major role in wound healing and abnormal scar formation, and α-SMA is the most reliable and widely used marker for the differentiation of fibroblasts into myofibroblasts, 5,31,32 and is assessed by western blot analysis. [33][34][35][36] Transforming growth factor-β1 (TGF-β1) is known to be a strong inducer of myofibroblast differentiation. We confirmed that TGF-β1 stimulation (20 ng/mL) increased α-SMA levels in both normal HDFs and HDFs from NF1 patients, although the basal expression of α-SMA before stimulation in NF1-derived HDFs tended to be higher than that of normal HDFs (Figures 2A and S2A,B).…”
Section: Dermal Fibroblasts Extracted From Nf1 Patients Do Not Differ...mentioning
confidence: 99%